Importance of reducing severe anterior vaginal prolapse during clinical examination and urodynamic study in the diagnosis of occult stress urinary incontinence - Rengifo, Rosa Reátegui (2013)
Objectives: To demonstrate the importance of reducing the high grade vaginal prolapse (POPQ> +III) in clinical and urodynamic evaluation when determining the presence of occult stress urinary incontinence and planning treatment of both conditions (prolapse and stress urinary incontinence - SUI) in the same surgical procedure in order to avoid SUI following correction of prolapse alone. Design: Retrospective and descriptive study. Setting: Urology, Clinica San Pablo, Sede Surco, Lima, Peru. Participants: Women with genital prolapse. Interventions: Between July 2009 and June 2012, in 40 patients 43-78 year-old (median 62,9 years) genital prolapse grade III-IV was reduced with gauze during both clinical evaluation and urodynamic study (SUI classification according to Continence International Society - SIC). Main outcome measures: Occult stress incontinence. Results: During clinical evaluation occult urinary stress incontinence was found in 19 patients (47.5%). Degree of prolapse according to POP-Q was +III in 14 (73.7%), +IV in 5 (26.3%); SUI according to SIC was I in 11 (57.9%), II in 7 (36.9%) and III in 1 (5.2%); there was no SUI type IV. Conclusions: Reduction of high grade vaginal prolapse (POPQ> +III) must be done by the gynecologist and urogynecologist during both routine clinical evaluation and urodynamic evaluation in order to either detect occult incontinence, plan correction of both conditions in one surgical act, and avoid a second operation for SUI correction and resulting legal issues. Not all patients with vaginal prolapse present occult stress urinary incontinence. Keywords: Severe genital prolapse, occult incontinence, urodynamics.